AB0404 Impact of Methotrexate in Mono- and Combined with Biologic Agents Therapy on Metabolic Syndrome Components in Early Rheumatoid Arthritis Patients. (9th June 2015) - Gorbunova, Y.; Popkova, T.; Kondratyeva, L.; Novikova, D.; Luchikhina, E.; Nasonov, E.
Abstract : Background: Metabolic syndrome (MeS) is a combination of cardiovascular complications risk factors (obesity, hyperglicemia, increasd triglycerides levels, dicreased HDL cholesterol levels, arterial hypertension), diagnosed in 19-55% rheumatoid arthritis (RA) pts. Objectives: To evaluate the impact of MT in mono- and combined with biologic agents therapy on MeS components in early RA pts after 24 weeks of treatment. Methods: Included 74 pts (54f/20m) with early RA (ACR/EULAR 2010 criteria), without prior therapy with GCs and DMARDs. Median age 56 [46;61] y, duration of the disease 6 [4, 0;8, 0] months, RF positive (87%), ACCP positive (100%); high RA activity (DAS28 5, 6 [5, 1;6, 4]). The following MeS components (NCEP/ATP III)were evaluated at baseline and after 24 weeks of therapy: WC≥102 cm (m)/≥88 cm (f), blood pressure ≥130/85 mmHg, hypertriglyceridemia - increased level of TG≥1, 7 mmol/l, decerased HDL cholesterol level <1, 0 mmol/l (m)/<1, 3mmol/l (f), increased fasting glucose level ≥6, 1 mmol/l. MeS was diagnosed in pts having ≥3 symptoms. All pts were administered subcutaneous methotrexate (SC MT)with dose escalation to 25-30 mg/week, in pts with poor response additional biologic agents therapy was administered in 12 weeks after initiation of SC MT (24pts - adalimumab; 9 - certolizumab pegol; 6 - abatacept; 1 - tocilizumab). Results: MeS prevalence in early RA pts prior to DMARDs intiation was 30%. Based on therapeutic regimens pts were grouped in two groups: I - MT monotherapy (n=34); II - combined therapy MT + biologic agents (n=40). Rates of decresaed HDL cholesterol levels were significantly higher at baseline in poor responders to MT monotherapy pts, requiring administration of biologic therapy, as compaired to pts with good response to MT therapy. After 24 weeks of therapy both groups demostrated improvement in HDL cholesterol levels and hypertriglyceridemia, more pronounced in MT therapy group. Dynamics in AO and hyperglycemia showed different trends: group I demonstrated decline in the rates of AO and hyperglycemia; group II - escalation in the rates of AO and hyperglycemia (p<0, 05). Comparable decrease in MeS rates was observed in both groups. Rate of remissions (DAS28<2, 6) by week 24 in group I was 47%, in group II -22, 5% (p<0, 05). Conclusions: In early RA pts rates of MeS decreased following the decline in disease activity after 24 weeks of "Treat to Target". In MT monotherapy group rates of all MeS components went down, except for eleated BP. Combined MT+ biologic, despite decreasing MeS rates, is associated with growing rates of AO and hyperglycemia, probaly due to short term treatment and lower precentage of pts achieving remission by 6 months of therapy. Disclosure of Interest: None declared